The Influence of Violin Tailpiece Material on Acoustic Properties of a Violin - ŁAPIŃSKI, Adam; SKRODZKA, Ewa Barbara; WICHER, Andrzej (Archives of Acoustics, 2024)
The different mechanical properties of the materials from which the tailpieces are made have a noticeable effect on the acoustic performance of the violin. These elements are made today from ebony, rosewood, boxwood, aluminium, or plastic. The aim of this study was to check the exact impact of tailpieces made of different materials on the frequency response function (FRF) of a violin’s bridge and the timbre of the instrument’s sound. For this purpose, the bridge FRF measurement was carried out, and a psychoacoustic test was conducted. The material from which the tailpiece is made to the greatest extent affects the modal frequencies in the range 530–610 Hz (mode B1+), which mainly manifested itself in a change in the instrument’s timbre in terms of the brightness factor. The study showed that the lighter the tailpiece, the darker the sound of the violin. It was also revealed that the selection of accessories affects factors such as openness, thickness, and overall quality ofthe sound.